Proteomic and Metabolomic Characteristics of Extremophilic Fungi Under Simulated Mars Conditions - Blachowicz, Adriana; Chiang, Abby J.; Elsaesser, Andreas; Kalkum, Markus; Ehrenfreund, Pascale; Stajich, Jason E.; Torok, Tamas; Wang, Clay C. C.; Venkateswaran, Kasthuri (Frontiers in Microbiology, 2019)
Filamentous fungi have been associated with extreme habitats, including nuclear power plant accident sites and the International Space Station (ISS). Due to immense adaptation and phenotypic plasticity capacities, fungi may thrive in what seems like uninhabitable niches. This study is the first report of fungal survival after exposure of monolayers of conidia to simulated Mars conditions (SMC). Conidia of several Chernobyl nuclear accident-associated and ISS-isolated strains were tested for UV-C and SMC sensitivity, which resulted in strain-dependent survival. Strains surviving exposure to SMC for 30 min, ISSFT-021-30 and IMV 00236-30, were further characterized for proteomic and metabolomic changes. Differential expression of proteins involved in ribosome biogenesis, translation, and carbohydrate metabolic processes was observed. No outstanding metabolome alterations were revealed. Lastly, ISSFT-021-30 conidia re-exposed to UV-C exhibited enhanced UV-C resistance when compared to the conidia of unexposed ISSFT-021.